Air and water : the biology and physics of life's media - Denny, Mark W., 1951- (Princeton University Press, 1993)
"Fish, shrimp, whales, and kelps live in the sea," writes Mark Denny, "and no one would mistake them for something that lives on land. By the same token, redwoods, hummingbirds, giraffes, and dragonflies are easily identified as being terrestrial." Denny's lively and informative book expands on this observation.